Bioadhesive chitosan nanoparticles: Dual targeting and pharmacokinetic aspects for advanced lung cancer treatment. (15th November 2021) - Vikas,; Viswanadh, Matte Kasi; Mehata, Abhishesh Kumar; Sharma, Vishal; Priya, Vishnu; Varshney, Neelima; Mahto, Sanjeev Kumar; Muthu, Madaswamy S.
Abstract: The chitosan-folate conjugate was synthesized initially and confirmed by FTIR and NMR spectroscopic studies. Following, docetaxel (DXL) loaded non-targeted, single receptor and dual receptor (folate and EGFR) targeted chitosan nanoparticles were prepared and their shape, particle size, zeta-potential, surface morphology and texture were screened by SEM, TEM, AFM analyses. Surface chemistry analysis by XPS indeed confirmed the successful conjugation of folate and cetuximab on the targeted formulations. In-vitro analysis of dual-targeted chitosan nanoparticles has revealed their superior cytotoxicity against A-549 cells. The IC50 of dual receptor-targeted chitosan NP was almost 34 times lower than DXL control. In-vivo pharmacokinetic study on Wistar rats has demonstrated improved relative bioavailability of all NP in comparison to DXL control. The results illustrated that EGFR and folate dual targeted NP enhanced the cytotoxicity of DXL towards A-549 lung cancer cells and substantially improved DXL pharmacokinetics in rats. Highlights: The chitosan-folate conjugate and carboxylated TPGS were successfully synthesized. DXL loaded dual receptor targeted chitosan NP were successfully prepared. C-6 loaded dual receptor targeted chitosan NP exhibited superior cellular uptake by A-549 cells. Dual receptor-targeted chitosan NP produced highest cytotoxicity (lowest IC50) against A-549 cells. All chitosan NP exhibited improved pharmacokinetics (relative to DXL control) in Wistar rats.